PENINGKATAN EKONOMI MANDIRI DAN KREATIF MELALUI SOSIALISASI STRATEGI PENINGKATAN LABA BAGI UMKM KABUPATEN TANAH LAUT - Bandi, Maulida Hirdianti; Hayatie, Marliza Noor; Machfiroh, Ines Saraswati; Karolina, Karolina (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2022)
Community Service Activities (PkM) is one of the Tri Dharma of Higher Education apart from education, teaching and research. The implementation of community service at the Tanah Laut State Polytechnic Accounting Study Program is to provide knowledge regarding Increasing the Independent and Creative Economy through the Socialization of Profit Increasing Strategies for Bangkit Indonesian MSMEs in Tanah Laut Regency. This activity was carried out in the Integrated Lecture Building Hall of the Tanah Laut State Polytechnic. There were 17 participants who took part in this event consisting of members of the community. The implementation of this activity involved 4 students, 4 lecturers and 5 students. Activities have been carried out by delivering material regarding Increasing the Independent and Creative Economy through the Socialization of Profit Increasing Strategies for Bangkit Indonesian MSMEs, Tanah Laut Regency.